Reading and writing in the academic community - Kennedy, Mary Lynch (Prentice Hall, 1994)
Reading and Writing in the Academic Community is a comprehensive rhetoric with engaging, timely readings. The authors wrote their book to include more coverage of the writing process to better meet the needs of students than other books in this market. The text presents the major types of academic writing students encounter as undergraduates while giving full consideration to the writing process and the basics of rhetoric. This text makes few assumptions about students' prior academic experience and provides explicit, step-by-step instruction in paraphrasing, summarizing, quoting, writing essays in response to readings, composing synthesis essays, and using sources to compose comparison-and-contrast essays, argument essays, analysis essays, evaluation essays, and research papers.